(untitled) (Perner’s Contacts, 2017)
The subject of the paper is the selection of the most suitable variant of transport between Southeast Asia and Slovakia using the decision-matrix method. Four major European seaports were selected for the comparison. The Asian port of Singapure is set as the starting point.